SISTEMATIC LITERATURE REVIEW: STRATEGI PENINGKATAN PRODUKTIVITAS KELAPA SAWIT DALAM MENGHADAPI PERUBAHAN IKLIM - Satria, Rievansyah Eka; Sofyan, Emma Trinurani; Sule, Marenda Ishak Sonjaya; Suriadikusumah, Abraham; Irwandhi (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Climate is an important factor which influences the growth and productivity of oil palm. The current oil palm cultivation system is vulnerable to climate change. For example, there was a decline in global oil palm production in 2015 due to ENSO, particularly affecting Southeast Asia. Extreme drought causes oil palm plants to experience water stress, while forest fires due to drought inhibit the photosynthesis process. A comprehensive study of the Systematic Literature Review was carried out using bibliometric analysis, systematic review and Meta-Analysis (PRISMA) methods, using the search engines Scopus and ScienceDirect with the keywords “palm AND oil AND production AND climate AND change”, “impact AND climate AND change AND coconut palm AND oil”, “palm AND oil AND adaptation AND climate AND change”, “palm AND oil AND mitigation AND climate AND change”. A thorough scientific literature review obtained 1331 papers from Scopus and ScienceDirect. Out of these, only 26 articles were selected for further examination. Based on the literature, there are several strategies for increasing oil palm productivity in the era of climate change. These strategies can be done through agronomic management, providing fertilizer from oil palm biomass, and maintaining irrigation for water availability. This literature study provides recommendations for strategies for increasing oil palm productivity in the face of climate change.